Shiva lingas carved on the stairs of the Kund - Temples of India Project Team (Jio Institute, 2024)
Small Shiva lingas (aniconic representation of Shiva) are carved on the stairs of the Kund. This suggests that the Kund served not only as a place for ritual bathing and cleansing but also as a significant location for offering prayers.